Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1155/2016/1925424
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Serum 25(OH)VD3, HIF-1α, VEGF, vWf, and IGF-1 and Their Correlation in Type 2 Diabetes Patients with Different Urine Albumin Creatinine Ratio

Abstract: Objective. To investigate changes in serum 25(OH)VD3, HIF-1α, VEGF, vWf, IGF-1, and their correlation in type 2 diabetes patients at different stages of diabetic kidney disease (DKD). Methods. 502 type 2 diabetes patients were divided into three groups: Normoalbuminuric group (201 patients), Microalbuminuric group (171 patients), and Macroalbuminuric group (130 patients). Serum 25-hydroxyvitamin D3 [25(OH)VD3] was measured by chemiluminescence. Serum hypoxia-inducible factor-1α (HIF-1α), vascular endothelial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 30 publications
(31 reference statements)
5
47
0
1
Order By: Relevance
“…Our findings, showing a significant decrease in VEGF following vitamin D treatment, are consistent with multiple previous studies [19,21,22,27,28]. In fact, Shao et al have recently shown that serum 25OH-D3 negatively correlates with VEGF in diabetic patients; such correlation suggests that the protective effects of vitamin D in terms of decreasing proteinuria and delaying the progression of diabetic kidney disease may be mediated through its suppression of abnormal angiogenesis, inflammation, and vascular endothelial dysfunction [19].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings, showing a significant decrease in VEGF following vitamin D treatment, are consistent with multiple previous studies [19,21,22,27,28]. In fact, Shao et al have recently shown that serum 25OH-D3 negatively correlates with VEGF in diabetic patients; such correlation suggests that the protective effects of vitamin D in terms of decreasing proteinuria and delaying the progression of diabetic kidney disease may be mediated through its suppression of abnormal angiogenesis, inflammation, and vascular endothelial dysfunction [19].…”
Section: Discussionsupporting
confidence: 94%
“…In fact, Shao et al have recently shown that serum 25OH-D3 negatively correlates with VEGF in diabetic patients; such correlation suggests that the protective effects of vitamin D in terms of decreasing proteinuria and delaying the progression of diabetic kidney disease may be mediated through its suppression of abnormal angiogenesis, inflammation, and vascular endothelial dysfunction [19]. Moreover, Ren et al have confirmed that 1,25(OH) 2 -D3 downregulates the expression of VEGF in the retinal tissues of diabetic rats, thereby protecting them against diabetic retinopathy [28].…”
Section: Discussionmentioning
confidence: 99%
“…Under hypoxic conditions such as in diabetes mellitus, HIF‐1α accumulates and induces expressions of certain factors including VEGF . Diabetes also elevated HIF‐1α and VEGF levels and increased levels were found related to diabetic kidney disease . In contrast, Sunkari et al found that HIF‐1α levels decreased in diabetic wounds in mice and hyperbaric oxygen therapy restored HIF‐1α levels and improved wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of plasma HIF-1α as a systemic cellular hypoxia biomarker in different clinical settings was previously confirmed (18). However, a few discrepant studies ascribed it in diabetes and other diseases (19)(20)(21)(22). It is well established that diabetes is characterized by defective angiogenesis, vasculopathy and poor wound-healing partly due to relative tissue hypoxia and reduced autophagy.…”
Section: Discussionmentioning
confidence: 91%
“…Homeostatic model assessment of IR showed positive correlation versus each of age, ABSI, BMI, AIP and CRP (particularly in controls) but negative correlation Serum HIF-1α increases and negatively correlates survival in non-diabetic patients with acute decompensated heart failure (20). Moreover, serum level of HIF-1α in T2DM patients is significantly higher than that in healthy controls and correlates with kidney function and disease duration (22). Specific allelic polymorphism in HIF-1α gene prevails in diabetic patients and complicated diabetes than healthy controls leading to a pathogenetic decrease in HIF-1α messenger ribonucleic acid expression irrespective of the oxygen conditions of cells (24).…”
Section: Correlation Analysismentioning
confidence: 94%